Review Implikasi Penggunaan Metode Pengeringan Vacuum Frying Pada Peningkatan Nilai Tambah Komoditas Buah dan Sayur - Mujahid, Abdullah; Damat, Damat; Harini, Noor (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
Vacuum frying is a promising food processing technology to increase the added value of fruit and vegetable crops. This technology involves frying at low pressure and lower temperatures compared to conventional frying. This article discusses the implications of using vacuum frying in increasing the added value of fruit and vegetable crops. The literature study method used is literature analysis from various related journals published in 2020 to 2024. The results of the literature study show that vacuum frying has several advantages over conventional frying, including: (1) producing products with lower oil content, (2) maintaining the original color, aroma, and taste of food ingredients, (3) maintaining nutritional content, (4) reducing oil absorption, and (5) produces a crispier texture. Vacuum frying has been successfully applied to various fruit and vegetable commodities, such as banana, jackfruit, mango, papaya, orange, salak, apple, yam, potato, mushroom, and asparagus. Literature studies show that vacuum frying can improve the quality of processed products, both in terms of nutrition, sensory, and shelf life. This technology also provides opportunities to develop new innovative and value-added products. This technology not only provides economic benefits for farmers and producers, but also contributes to the provision of healthy and nutritious food for the community. Further research is needed to optimize the use of vacuum frying on various commodities and develop innovative new products.